APPLICATION OF HIGH-PRESSURE LIQUID CHROMATOGRAPHY FOR ANALYSIS OF LARD IN THE MEATBALL PRODUCT COMBINED WITH PRINCIPAL COMPONENT ANALYSIS - Ahda, Mustofa; Guntarti, Any; Kusbandari, Aprilia (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The aim of this research to design the discriminant method of pork and beef meatball using high-pressure liquid chromatographyultraviolet (HPLC-UV) combined with principal component analysis. Methods: The 100% pork and 100% beef meatball was analyzed using HPLC-UV. The all chromatogram data from HPLC were processed using chemometrics method especially principal component analysis for discriminant the pork and beef meatball. Results: The results showed that the beef and pork meatball can be distinguished using HPLC which was combined principal component analysis. However, the application of HPLC has a problem for lard detection in meatball because cannot to control the hydrolysis of triglyceride (TGA). Hydrolysis of TGA can also be detected using HPLC-UV and giving the interference for halal authentication. Conclusion: The discriminant process of pork and beef meatball using HPLC-UV has a problem in TGA analysis. The TGA will be hydrolyzed to diglycerides, monoglyseride, and fatty acid form. All products from hydrolysis of TGA will give the interference in the discriminant process.